ANALYSIS OF CARDIORESPIRATORY FITNESS AMONG ATHLETE STUDENTS (The Research of Medical Science Review, 2025)
Background: Cardiorespiratory fitness (CRF) reflects the capacity of the heart, lungs, and circulatory system to deliver oxygen during sustained exercise.Objective: To evaluate the cardiorespiratory fitness of university athlete students using the Modified Harvard Step Test.Methods: A cross-sectional study was conducted at the University of Management and Technology (UMT), Lahore. A total of 137 athlete students aged 18–27 years participated. Physical Fitness Index (PFI) was calculated using the Modified Harvard Step Test. Demographic data, BMI, and PFI were analyzed with SPSS Version 25.Results: The mean age was 22.21 ± 2.16 years; mean BMI was 30.21 ± 4.17 kg/m². The average PFI was 83.10 ± 12.76. Among participants, 44.53% demonstrated excellent CRF, 27.74% good, 22.63% high average, and 5.11% low average levels. Significant differences in PFI and BMI were found between male and female students (p < 0.01).Conclusion: University athlete students generally exhibited satisfactory cardiorespiratory fitness. Ongoing assessment and encouragement of exercise are recommended to maintain and improve CRF